Information, Sharing, and Self-Determination: Understanding the Current Challenges for the Improvement of Pediatric Care Pathways - Scopetti, Matteo; Santurro, Alessandro; Gatto, Vittorio; Padovano, Martina; Manetti, Federico; D'Errico, Stefano; Fineschi, Vittorio (Frontiers in Pediatrics, 2020)
Despite the considerable progress of medical science over the years, pediatric patients can still be affected by serious illnesses that, regardless of age, lead to experiencing all the clinical, psychological, ethical and spiritual problems related to incurable diseases and death. The interaction between the peculiarities of individuals, and the clinical conditions presented define a changing and complex profile of health needs, which requires organized, dynamic and multidimensional responses. The approach to the pediatric patient must consider its biological, psychological, relational and clinical characteristics. Such aspects in fact determine and modulate the type and quantity of the needs presented, conditioning the actions to be taken and the organizational models to be implemented. In accordance with some international regulations, it is essential that healthcare professionals provide adequate information to the patient's understanding in order to enhance participation in the decision-making process regardless of the possibility of expressing consent or dissent to the treatment. Frequently, the sharing of decisions on the care path not only fails to involve children, but often lacks rigorously designed interventions for parental involvement. Therefore, the development of care models that focus on the needs of the pediatric population is crucial. The present paper aims to analyze the problems of information quality and sharing in pediatric care pathways in order to promote shared decision-making and improve the knowledge of the professionals involved. As a secondary objective, the study will provide useful insights for the prevention of decision-making conflicts frequently at the basis of the dispute in the pediatric field.